Strategy To Build Competitiveness Public Health Study Program Case Study At Stikes Bhakti Pertiwi Indonesia - Haura Kalina; Aulia Hervi Anggraini; Ratna Utami Wijayanti; Wahyu Wismanto Hadi (CV. Inara, 2022)
Higher education has a strategic role and responsibility in participating in the development of a nation. Higher education can help solutions including solving educational problems, from the elementary level to college. Within that framework, the role of higher education institutions reflected in the Tri Dharma function of higher education, namely education, research and community service can help develop the concept and implementation of basic education strategies to higher education. Implementation is done by the pattern of cooperation between education policy makers, educational institutions, society and industry as the last user of graduates from the world of Education. Similarly, in health colleges such as Stikes Bhakti pertiwi Indonesia in the Public Health Study program, the participation of the community, government, industry and related institutions synergize in order to create quality human resources and international capacity so as to have global competitiveness. People who increasingly understand information in today's digital era, assess the absorption of graduates in quality schools is one of the criteria for the quality of an educational institution. This is also the reason for competition between higher education institutions such as in the Public Health Study program which is so tight today. This condition is real on the other hand raises the desire and interest of capital owners to invest in the establishment of higher health education. Commercialization of education is not appropriate, but professional management is a must, good management conditions, credible and accountable increasingly urgent to do by the management of higher education managers. If this is not done, the institution will only be displaced by various new educational institutions that appear. Educational institutions that do not want to adapt to progress will only survive without motivation to progress and develop. A competitive higher education institution such as Stikes Bhakti Pertiwi Indonesia which has a well-managed and healthy public health study program will be seen from the dynamics of the program that is adaptive to the Times. The professionalism of the manager will be seen how fully an institution has a unity of steps towards progress and is able to compete with other competitors. It should be realized that currently the number of private educational institutions at all levels if taken on average about 68% managed by the community so that competition is complex and open. Healthy organization in an institution, among others, is determined by good management and leadership. The development of the Indonesian nation in the future is determined in the development of health human resources, especially those that rely on the long-term vision of Indonesia, namely the realization of a modern Indonesian nation-state that is safe and peaceful, fair and democratic, and prosperous by upholding human values, independence and unity based on Pancasila and the 1945 Constitution.